Using economic values to evaluate management options for fish biodiversity in the Sikakap Strait, Indonesia (Biodiversitas Journal of Biological Diversity, 2017)
Rizal A, Dewanti LP. 2017. Using economic values to evaluate management options for fish biodiversity in the Sikakap Strait, Indonesia. Biodiversitas 18: 575-581. The unavailability of total economic values of fish biodiversity in Sikakap Strait, Mentawai District of West Sumatra, Indonesia both in the short and long term, has created the rejection of their existences in the coastal area. The purpose of this study was to estimate the total economic value of fish biodiversity in Sikakap Strait, West Sumatra using total economic value concepts. The fish biodiversity’s total economic value is expressed by estimating the use value, indirect use value and non-use value. The study used benefit transfer and survey methods using secondary data to estimate the total economic value of fish biodiversity. The total economic value of the fish biodiversity of USD 745,602 per year was calculated by summing the direct use value (USD 4,262,884 per year), indirect use value (USD 24,560 per year), and non-use value (USD 575 per year). The research hypothesis that the fish biodiversity’s sustainable resource management has economic value is supported. These values help to make decisions about allocating resources between competing uses.
Keywords: economic valuation; fish biodiversity; Sikakap Strait